2019
DOI: 10.1108/k-04-2018-0212
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical mentoring and transformation of teaching practices in university

Abstract: Purpose The purpose of this paper is to identify how pedagogical mentoring contributed to the transformation of teachers’ pedagogical practices and to the consolidation of a team of autonomous leaders in a Colombian regional university, within the framework of a curricular reform. Design/methodology/approach The paper is a qualitative research under the methodology of experience systematization. In this methodology, the participants and researchers analyze experiences and generate knowledge about why process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…It is also suggested that to identify and formulate new ways and means of funding of the schools of governance, independent and extensive studies be conducted. Based on the components “establishment of research centers and institutions,” “conducting applied and operational research,” “production of new governance and public policy knowledge” (Table IX), and to aid the promotion of the governance school's educational system, particularly in the components “workshop,” “case studies,” and “use of advanced technologies,” it is suggested that the schools of governance establish satellite institutions such as governance lab for operationalizing and localizing the existing knowledge about governance (for example, see the Government Performance lab, Kennedy School of Government (Harvard University), Governance Lab of the Tandon School of Engineering). Based on the components “experience and expertise,” “spirit of public service,” “spirit of leadership,” “experience of administrative, managerial and policymaking positions” (Table VI) and the components “workshop,” “case studies,” “attendance by politicians, elites, and government executives” and “visits to policy centers and offices of public officials,” (Table VIII) the mentoring method and presentation of professional training courses at the schools of governance is a principle. Correspondingly, it is suggested that the faculty members of these schools should become the basis of education and act as autonomous mentors (Hernandez and Flores, 2019). Thus, the faculty members of the schools of government/governance, as presented in Table VII, must be selected from among the professionals with a strong background and the education programs should be shaped based on their successful experience in governance.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also suggested that to identify and formulate new ways and means of funding of the schools of governance, independent and extensive studies be conducted. Based on the components “establishment of research centers and institutions,” “conducting applied and operational research,” “production of new governance and public policy knowledge” (Table IX), and to aid the promotion of the governance school's educational system, particularly in the components “workshop,” “case studies,” and “use of advanced technologies,” it is suggested that the schools of governance establish satellite institutions such as governance lab for operationalizing and localizing the existing knowledge about governance (for example, see the Government Performance lab, Kennedy School of Government (Harvard University), Governance Lab of the Tandon School of Engineering). Based on the components “experience and expertise,” “spirit of public service,” “spirit of leadership,” “experience of administrative, managerial and policymaking positions” (Table VI) and the components “workshop,” “case studies,” “attendance by politicians, elites, and government executives” and “visits to policy centers and offices of public officials,” (Table VIII) the mentoring method and presentation of professional training courses at the schools of governance is a principle. Correspondingly, it is suggested that the faculty members of these schools should become the basis of education and act as autonomous mentors (Hernandez and Flores, 2019). Thus, the faculty members of the schools of government/governance, as presented in Table VII, must be selected from among the professionals with a strong background and the education programs should be shaped based on their successful experience in governance.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Based on the components “experience and expertise,” “spirit of public service,” “spirit of leadership,” “experience of administrative, managerial and policymaking positions” (Table VI) and the components “workshop,” “case studies,” “attendance by politicians, elites, and government executives” and “visits to policy centers and offices of public officials,” (Table VIII) the mentoring method and presentation of professional training courses at the schools of governance is a principle. Correspondingly, it is suggested that the faculty members of these schools should become the basis of education and act as autonomous mentors (Hernandez and Flores, 2019). Thus, the faculty members of the schools of government/governance, as presented in Table VII, must be selected from among the professionals with a strong background and the education programs should be shaped based on their successful experience in governance.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%
“…Sin embargo, las universidades en sí mismas son organizaciones que se estabilizaron en el siglo XIX y en donde priman las pedagogías tradicionales, con currículos centrados en los contenidos [1] y orientados al desarrollo de las disciplinas como campos particulares de saber. Así, afrontan retos importantes para movilizarse a propuestas pedagógicas innovadoras donde los currículos se orienten al desarrollo de competencias y pueda evidenciarse qué y cómo aprenden los estudiantes [2]- [5].…”
Section: Introductionunclassified